False-negative rate cannot be reduced by lowering the haemoglobin concentration cut-off in colorectal cancer screening using faecal immunochemical test. Issue 5 (September 2017) - Ibañez-Sanz, Gemma; Garcia, Montse; Milà, Núria; Rodríguez-Moranta, Francisco; Binefa, Gemma; Gómez-Matas, Javier; Benito, Llúcia; Padrol, Isabel; Barenys, Mercè; Moreno, Victor
Abstract : The aim of this study was to analyse false-negative (FN) results of the faecal immunochemical test (FIT) and its determinants in a colorectal cancer screening programme in Catalonia. We carried out a cross-sectional study among 218 screenees with a negative FIT result who agreed to undergo a colonoscopy. A false-negative result was defined as the detection, at colonoscopy, of intermediate/high-risk polyps or colorectal cancer in a patient with a previous negative FIT (<20 µgHb/g). Multivariate logistic regression models were constructed to identify sociodemographic (sex, age) and screening variables (quantitative faecal haemoglobin, colonoscopy findings) related to FN results. Adjusted odds ratios and their 95% confidence intervals were estimated. There were 15.6% FN FIT results. Faecal haemoglobin was undetected in 45.5% of these results and was below 4 µgHb/g in 94.0% of the individuals with a FN result. About 60% of the lesions were located in the proximal colon, whereas the expected percentage was 30%. Decreasing the positivity threshold of FIT does not increase the detection rate of advanced neoplasia, but may increase the costs and potential adverse effects.